Synthesis of 5-oxo(thioxo)-5,6-dihydro-tetrazolo[1,5-c]quinazoline, qsar modeling and anticancer activity - Antypenko, O. M. (Запорізький державний медичний університет, 2015)
The aim: to calculate QSAR-models of anticancer activity using the data of our previous articles. Using this models, to predict structures with high growth percentage and to synthesize them. Materials and methods: the genetic algorithm (GA) and multiple linear regression analysis (MLRA) were used to select the descriptors and to generate the correlation models, that relate the structural features to the cell growth percent of different cancer cell lines.
Keywords: тези